PENGARUH KUALITAS PELAYANAN, FASILITAS, HARGA DAN PRODUK TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Loris Beauty Clinic Malang) - Melinda Handayani; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTTo find out and analyze the influence of service quality, facilities, prices and products on customer satisfaction Loris Beauty Clinic Malang. The population in this study were Malang Loris Beauty Clinic customers who performed for 3 months, namely as many as 960 who would be respondents in this study. And it has been calculated using the Slovin formula to become 91 respondents. Data collection through questionnaires. Analysis of the data in this study using SPSS version 16. And the sampling technique using non probability sampling methods and data testing techniques used in this study include validity test, reliability test, classic assumption test and multiple linear regression analysis, and testing the research hypothesis.The results of the analysis show that service quality, facilities, prices and products in partial tangible, facilities and products have a positive and significant influence, but the service quality variable has a positive but not significant effect. And the price variable has no significant effect. Keywords: Service Quality, Facilities, Prices, Products and Customer Satisfaction